Comparative study between Preemptive Thoracic Epidural Analgesia and conventional postoperative Thoracic Epidural Analgesia in Thoracic Surgery - Kalam, Farzana; Hossain, Pervez Altaf; Masum, Abdullah (Journal of the Bangladesh Society of Anaesthesiologists, 2022)
Background : The aim of this study is to compare and to observe the effectiveness of preemptivethoracic epidural analgesia (TEA) with conventional postoperative epidural analgesia in thoracotomy.Material and Methods: Forty patients were randomized in to two groups (preemptive Group: Group P,control: Group C). Epidural catheter was inserted in all patients preoperatively. In Group P, epiduralanalgesic solution was administered as a bolus before the surgical incision and was continued until theend of the surgery. Postoperative patient controlled epidural analgesia was introduced via syringe pumpsfor all patients. Respiratory rates (RR) were recorded. Patient’s analgesia was evaluated with visualanalog scale at rest (VASr) and coughing (VASc). Number of patient’s demands from the pump andadditional analgesic requirement were also recorded. Results : RR in Group C was higher than in Group P at postoperative 1st and 2nd hours. Both VASrand VASc scores in Group P were lower than in Group C at postoperative 1st, 2nd, and 4th hours.Patient demand and bolus delivery count from pump in Group P were lower than in Group C in allmeasurement times. Total analgesic requirements on postoperative 1st and 24th hours in Group P werelower than in Group C. Conclusion: From the study we consider that preemptive TEA may offer better analgesia afterthoracotomy. JBSA 2022; 35 (1) : 23-29